Cost-Benefit Analysis of Antimicrobial Stewardship Program in the Adult General Medicine Setting in Qatar - Dina Abushanab (10696501) (2024)
Background There is a lack of evidence regarding the economic impact of antimicrobial stewardship program (ASP).We sought to evaluate the cost-benefit of the mature ASP use compared to premature ASP use in the adults’ general medicine settings in Qatar. Methods Patient records were retrospectively reviewed during two periods: premature ASP (i.e. the 12 months following ASP implementation (May 2015-April 2016)), and mature ASP (i.e. the last 12 months of a 5-year ASP implementation in Hamad Medical Corporation (HMC) (February 2019-January 2020)). The economic benefit of the ASP maturity was calculated as the sum of the cost savings and the cost avoidance, minus the operational cost of the service.3 The cost savings were the reduced cost of therapy associated with an assumed reduction in defined daily dose and resource utilization because of the ASP maturity. Cost avoidance was the cost avoided by reducing length of hospitalization and adverse drug events. Operational costs included the monetary value of the time spent in data collection, clinical rounds, and committee meetings. A total of 500 patients were randomly included (250 in each cohort). Results The operational costs of the program decreased with maturity by cost savings of QAR125 per 100-patient beds per year. Antimicrobials use and resource utilization, and their associated costs, declined after the maturity of ASP (i.e. positive cost saving), with a cost saving of QAR 458 (US$ 125) per 100-patient beds per year, signifying a benefit of QAR 458 generated for each QAR 1 invested in the ASP service. The avoided cost was in negative, by QAR -4,807 per 100-patient beds, in favour of the premature period. Sensitivity analyses indicated a 100% probability that maturity is linked with a positive benefit-to-cost ratio (Figures 1 and 2). Conclusion We showed that substantial savings in healthcare costs can be achieved through the maturity of ASP, even when accounting for ASP operational costs.